Acute Toxicity And Diuretic Activity Of Mangifera Indica L. Bark Extracts - M.S.SHREE DEVI, (International Journal of Pharma and Bio Sciences, 2011)
Introduction: Kidney, the excretory organ of our body serves the important function of excretion of waste products, regulation of fluid volume and electrolyte content of the extracellular fluid. Diuretics are drugs capable of increasing levels of urine. Materials and methods: The Ethyl acetate, ethanol and water extract of Mangifera indica was evaluated for diuretic activity. Diuretic effect was carried out in rats (175 – 200 kg bwt) by measuring the urine volume by 1, 2, 4, 6 hours and later at 24 hours. Positive control was furosemide (20mg/kg) intraperetoneally and mannitol (100mg/kg) intravenously given. The extracts were administered orally at the dose of 250 mg/kg b.wt. Preliminary phytochemical tests were carried out in different extracts. Results: Na+, K+ and Cl- concentrations were determined. Na+/ K+ ratio was higher in aqueous extract and followed by ethanol and ethylacetate extracts. The aqueous extracts show best diuretic effect when compared with other extracts. Conclusion: It was determined that all the extracts showed diuretic effect and cation excretion outstandingly.